Quercetin-POM (pivaloxymethyl) conjugates: Modulatory activity for P-glycoprotein-based multidrug resistance - Kim, Mi Kyoung; Park, Kwang-Su; Choo, Hyunah; Chong, Youhoon (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2015)
Background: We previously demonstrated that the bioactivity of quercetin could be improved through conjugation with a hydrolysable pivaloxymethyl (POM) group. Purpose: Present study aimed to evaluate MDR (multidrug resistance)-modulatory activity of the quercetin-POM conjugates. Study design/methods: MDR-modulatory activity was determined by measuring cytotoxicity of various anticancer agents to MDR MES-SA/Dx5 cell lines upon combination with the quercetin-POM conjugates. Results: The quercetin-7-O-POM conjugate (7-O-POM-Q) was significantly more potent than quercetin in reversing MDR, which recovered the cytotoxicity of various anticancer agents with EC50 values of 1.1-1.3 mu M. A series of mechanistic studies revealed that 7-O-POM-Q competes with verapamil in binding to the same drug-binding site of the major MDR target, Pgp (P-glycoprotein), and inhibits Pgp-mediated drug efflux with a similar potency as verapamil. The physicochemical properties of 7-O-POM-Q were then evaluated, which confirmed that 7-O-POM-Q has remarkably enhanced cellular uptake and intracellular localization compared with quercetin. Additionally, it is noteworthy that 7-O-POM-Q undergoes slow hydrolysis to quercetin over a prolonged period of time. Conclusion: The quercetin-POM conjugate showed significantly improved MDR-reversing activity compared with quercetin, which could be attributed to its capacity to maintain high intracellular concentrations. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: IN-VITRO; FLAVONOID QUERCETIN; FLOW-CYTOMETRY; CELL-LINES; METABOLISM; VIVO; ACCUMULATION; INHIBITORS; MECHANISM; EFFLUX